Comparison of Syringe Compression Force Between ENFit and Legacy Feeding Tubes. Issue 1 (30th May 2018) - Mundi, Manpreet S.; Duellman, Wanda; Epp, Lisa; Davidson, Jacob; Hurt, Ryan T.
Abstract: Background : Since initial report in 1972, misconnections continue to be an issue, especially in hospitalized patients with multiple access devices. A new small‐bore connector standard (ENFit) has been proposed in order to minimize misconnections. Methods : Commercially available finalized ENFit tubes of a variety of sizes (14 French [Fr] size, 18Fr, 20Fr, 24Fr, and low‐profile) were obtained for current testing. Variety of commercially available formulas including blenderized tube feeding (BTF) products (Jevity 1 Cal, Abbott Nutrition, Abbott Park, IL; Nourish, Functional Formularies, Centerville, OH; Real Food Blends, Chesterton, IN) were tested. Results : Data from individual measurements were aggregated for ENFit and legacy tubes and revealed higher syringe compression force in legacy tubes compared with ENFit tubes for 20Fr size with Jevity formula. Our institution's BTF formula revealed that legacy tubes had lower syringe compression force than ENFit tubes for 14Fr tube size. Remaining measurements revealed no significant difference. Model 1 of regression analysis revealed that only formula and tube size were significant with R 2 of 0.63. Model 2 evaluating the impact of tube size, blender, time of blending, and legacy vs ENFit revealed that tube size, blender used, and blending time were significant with legacy vs ENFit being nonsignificant (R 2 of 0.72). Conclusions : Overall, only a small number of tube sizes (14Fr and 20Fr) with selected formulas revealed a significant difference between ENFit and Legacy tubes, with remaining studies finding no significant difference. Regression analysis revealed that variables such as formula, size of tube, blender used, and time of blending may have more impact on compression force.